Reseña de los escritos de Marx sobre América Latina en Alberto Fillipi - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
The following article is aimed at re-think about the reaches and limitations on one of most known Latin-American politic researchers in XX century. Even though, most of his historic researches are around Venezuela or Grand Colombia, Alberto Fillipi is considered (actually) one of the most important historian who has been dedicated on latinoamerican institution. In the work Las Instituciones e Ideologías en la Independencia Hispanoamericana Fillipi sustain the vision of Karl Marx about the Americas. Precisely, our paper is a humble intention to lead light about this work.